ISOLATION AND CHARACTERIZATION OF ALCOHOL TOLERANT LIPASE FROM COMPOST MICROORGANISM FOR BIODIESEL - Asfarina, Hasti
Lipase (triacylglycerol acylhydrolases, EC 3.1.1.3) is an enzyme that catalyze the hydrolysis of ester bond in triacylglicerol and catalyze the transesterification with alcohol. Lipase is a potential biocatalyst for applications in many industrial fields such as the food industry, oil industry, health industry, cosmetics industry, and detergents industry. Moreover, lipase has been developed as biocatalyst in the synthesis of biodiesel. In the process of biodiesel synthesis, required a lipase that is tolerant to alcohol which is one of the reactant in the enzymatic process. Therefore, it is necessary to find a lipase that catalysis in high concentration of alcohol. Lipase can be isolated from almost all living things, both higher organisms like animals and plants as well as low organisms such as fungi and microorganisms. Most potential source to isolate lipase is microorganisms because it grows faster and more various lipase could be obtained. Alcohol tolerant microorganisms are required this term to obtain alcohol tolerant lipase. This microorganisms were isolated from thermophilic phase of household-compost, since household compost microorganisms were assumed to be more alcohol and organic solvent tolerant compared to those of other sources because the compost microorganisms lives in various mixes waste and organic compounds. Compost used in this study was sampled at thermophilic phase in the process of composting. The research stage is consist of the selection of alcohol tolerant microorganisms that produce lipase, identification of alcohol tolerant bacteria that produce lipase, bacteria cultivation and isolation of lipase, and characterization of hydrolysis and transesterification lipase activity. Selection of alcohol tolerant microorganisms carried by Luria Bertani medium containing 8% alcohol at 55o C. Several isolates alcohol tolerant microorganisms was tested for lipase activity qualitatively using olive oil, tween 80, and rhodamine B. Growth curve of two isolates that has most fluorescent rays was established and hydrolase activity was determined quantitatively every hour. Both isolates had the highest hydrolysis activity after 15 hour growth. One isolate whose higher activity was selected for other characterization of microorganisms and lipase. v The selected isolate identified as gram-positive rod-shaped bacteria and ribotyping analysis showed 99% identical with Aeribacillus pallidus bacteria. Variations of short, medium and long chain substrate in hydrolysis activity of crude extract lipase has been tested, the result showed that hydrolase activity were more selective to selected p-nitrophenyl laurate substrate (medium chain). Crude extract lipase were also tested to the resilience of alcohol and showed stability, since it still have 75.66% of the original activity upon the addition 20% of alcohol. Fractionation of the crude extract was carried out using ammonium sulfate fractionation graded from 0-30%, 30-60% and 60-80%. Zimogram native PAGE results showed the active lipase in each fractions. Molecular weight of lipase was determined using SDS-PAGE showed that it siza was 44 kDa. The highest hydrolysis activity was obtained in 0-30% fraction which has the characteristics of an optimum pH at 8.5 and optimum temperature at 65 o C. To get a lipase that can be used as a biocatalyst of biodiesel, transesterification activity was also conducted in each fractions. The highest transesterification activities were also obtained in 0-30% fraction with its conversion was 18.895% and had the optimum temperature at 45 o C. Determination of kinetic parameters showed that Vmaxapp value were calculated as 0.137 ?mol/mg minute in hydrolysis activity and 8.946% conversion/minute in transesterification activity, Kmapp value were calculated as 0.9 mmol/L in hydrolysis activity and 59.373 mmol/L in transesterification activity, and Kcatapp value were calculated as 0.019 minute-1 in hydrolysis activity and 18.408 minute-1 in transesterification activity. Characteristics of lipase alcohol tolerant with transesterification activity were expected to be potential biocatalyst for biodiesel.